Nuclear Lamin B1 Interactions With Chromatin During the Circadian Cycle Are Uncoupled From Periodic Gene Expression - Brunet, Annaël; Forsberg, Frida; Fan, Qiong; Sæther, Thomas; Collas, Philippe (Frontiers in Genetics, 2019)
Many mammalian genes exhibit circadian expression patterns concordant with periodic binding of transcription factors, chromatin modifications and chromosomal interactions. Here we investigate whether chromatin periodically associates with nuclear lamins. Entrainment of the circadian clock is accompanied, in mouse liver, by a net gain of lamin B1-chromatin interactions genome-wide, after which the majority of lamina-associated domains (LADs) are conserved during the circadian cycle. We nevertheless detect hundreds of variable interactions among which oscillations occur at 64 LADs, affecting one or both LAD extremities or entire LADs. Only a small subset of these oscillations however exhibit highly significant 12, 18, 24 or 30 h periodicity in our dataset. Periodic LADs display oscillation asynchrony between 5’ and 3’ LAD borders, and are uncoupled from periodic gene expression within or in vicinity of these LADs. Periodic gene expression is also unrelated to the gene-to-nearest LAD distance variation detected during the circadian cycle. Accordingly, periodic genes, including central clock-control genes, are located megabases away from LADs throughout circadian time, suggesting stable residence in a transcriptionally permissive chromatin environment. We conclude that periodic LADs are not a dominant feature of variable lamin B1-chromatin interactions during the circadian cycle in liver. Our results also suggest that periodic hepatic gene expression is not regulated by rhythmic chromatin associations with the nuclear lamina.